Association of long cardiac troponin T forms with adverse long-term outcomes in patients with advanced chronic kidney disease - Salonen, Selma; Kaipainen, Emilia; Hakamäki, Markus; Liuhto, Niilo; Manni, Noora; Toukola, Tomi; Virtanen, Jonna; Lankinen, Roosa; Metsärinne, Kaj; Vasankari, Tuija; Airaksinen, K. E. Juhani; Järvisalo, Mikko J.; et al. (BioMed Central, 2026)
Background
Commercial high-sensitivity cardiac troponin T (hs-cTnT) assays measure both intact and degraded cTnT forms (i.e. total cTnT) and values are often elevated in chronic kidney disease (CKD) patients. The measurement of long cTnT forms has recently shown improved specificity for acute myocardial infarction compared to total cTnT. However, the associations between long cTnT and adverse long-term outcomes in CKD are unknown.
Methods
Altogether, 136 CKD stage 4–5 patients not on dialysis were included in this prospective cohort study. Long cTnT and total cTnT levels before dialysis initiation were measured using investigational in-house immunoassays. The associations between cTnT measurements and all-cause mortality, incident major adverse cardiovascular or cerebrovascular events (MACCE), new-onset atrial fibrillation (NOAF) and a composite adverse outcome (all-cause mortality or MACCE) were assessed.
Results
Mean age was 61 (±13) years, 47 (34.6%) were female and median values for long cTnT and total cTnT were 1.9 (1.3–3.0) ng/L and 37 (23–66) ng/L, respectively. After a median follow-up of 6.2 (4.6–7.7) years, 62 (45.6%) patients had died, 36 (26.5%) had experienced MACCE, 28 (23.3%) NOAF and 76 (55.9%) a composite adverse outcome. In multivariable Cox models adjusted for age, sex and coronary artery disease (CAD), long cTnT and total cTnT were independently associated with all-cause mortality, NOAF and the composite adverse outcome, while only total cTnT was associated with MACCE. Replacing the adjustment for CAD with kidney transplantation in the multivariable models weakened the significance of the associations.
Conclusions
We describe for the first time associations between long cTnT and long-term cardiovascular adverse outcomes and all-cause mortality in a prospective cohort of CKD stage 4–5 patients.